Chlorophyll and Morphological Mutations Induced by Chemical Mutagens EMS, DES in (Setaria italica(L.)Beauv.)Var .CO(Te)7 in M2 Generation - Anittha, I.; Mullainathan, L. (International Journal of Scientific Research in Biological Sciences, 2018)
The assessment of mutagen concentration is typically evaluated by the morphological and chlorophyll mutants. Setariaitalica var. CO(Te)7 Fox tail millet seeds were treated with the chemical mutagens namely EMS in the concentration 20, 30,40 mM and DES in the concentration 30, 40 and 50 mM . The present investigation reveals chlorophyll mutants like Albino, Chlorina, Xantha , Straita and various morphological mutants like Tall plant, Dwarf plant, Long spike, Short spike, multiple spike ,Long awn spike, Thumb branch spike, Bold seed, Sterile spike, Tip sterile spike, Anthocyanin pigment in spike, Helical spike, Brachytic, Tiller, Zebra striped, Early and late maturity mutants were observed in M2 generation. The primary objective of the research work was to increase the availability of our traditional millet variety Tenai which was a balanced nutricereale and can be cultivated in large scale with the superior quality. They can be screened and enhanced through mutation breeding for enormous yield. The effect of EMS shows more chlorophyll and morphological mutants than DES in fox tail millet.